A Continuous DUE Algorithm Using the Link Transmission Model - Nezamuddin, N.; Boyles, Stephen D. (Networks and spatial economics, 2015)
This paper describes a continuous-flow, continuous-time model for which a dynamic Wardrop equilibrium provably exists. This formulation is general, but is particularly designed to include the link and node models of Yperman’s Link Transmission Model as a special case. Rather than using path flows to describe route choice, travelers are aggregated by destination and node-specific routing parameters are used to reduce the number of control variables needed. Furthermore, this formulation allows efficient solution methods from static traffic assignment, such as Linear User Cost Equilibrium (LUCE), to be applied in a fairly straightforward manner. Demonstrations on a small network verify the effectiveness of this dynamic LUCE algorithm in our model, showing favorable performance comapred to the method of successive averages.